REKONSTRUKSI PÉSO PANGOT SUNDA UNTUK MEDIA PEMBELAJARAN MENULIS AKSARA TRADISIONAL - Permadi, Tedi (Pusat Riset Manuskrip, Literatur, dan Tradisi Lisan, 2023)
This article describes the efforts to reconstruct the traditional Sundanese writing instruments, namely péso pangot to write on lontar. The problems faced stem from the cultural fact that the tradition of writing lontar in Sundanese has become extinct since the 17th century. The theory used is a codicological study, especially mediums, and techniques related to writing tools. The descriptive analysis research method was used to describe the material, form, manufacture, and how to use Sundanese péso pangot as a medium for learning to write a traditional script. The benefits include providing direct knowledge, understanding, and experience in learning to write traditional scripts, providing alternative activities for the development of Sundanese culture in the context of written tradition-based learning, and allowing the activities to be duplicated in various forms that involve the active participation of the community.